1983
DOI: 10.1210/jcem-56-4-781
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR3 and HLA-DR5 Associated Thyrotoxicosis-Two Different Types of Toxic Diffuse Goiter*

Abstract: One hundred fifty patients with toxic and scintigraphically diffuse goiter were HLA typed (A, B, C, DR). One group consisted of 101 patients with concomitant Graves' ophthalmopathy and/or TSH-binding inhibiting antibodies (TBIAb). Forty nine patients had neither ophthalmopathy nor TBIAb. The former group showed a higher prevalence of HLA-B8 and DR3 compared to a normal control group. The latter group showed a higher frequency of HLA-DR5, whereas the HLA-B8 and DR3 antigens were slightly below normal prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 35 publications
2
23
2
Order By: Relevance
“…The association of the 8-kb Eco RI CX allele with Graves' disease described here is of considerable interest and probably should now be analyzed with respect to HLA-DR or immunoglobulin Gm or Km allelic distributions similar to those which have been performed in the past (39)(40)(41)(42)(43). On the basis of the findings presented here, it would now appear appropriate to again examine additional markers on lambda Ig light chains such as those recently described (44) for a possible correlation to the CX genotypic profiles described in the present study.…”
Section: Discussionmentioning
confidence: 82%
“…The association of the 8-kb Eco RI CX allele with Graves' disease described here is of considerable interest and probably should now be analyzed with respect to HLA-DR or immunoglobulin Gm or Km allelic distributions similar to those which have been performed in the past (39)(40)(41)(42)(43). On the basis of the findings presented here, it would now appear appropriate to again examine additional markers on lambda Ig light chains such as those recently described (44) for a possible correlation to the CX genotypic profiles described in the present study.…”
Section: Discussionmentioning
confidence: 82%
“…One interesting feature of many peptides identified was their theoretical "promiscuity", that is, their capability to bind to many different HLA-DR alleles, which may be related to autoreactive TCR degeneracy. In fact, DR association with thyroid diseases is not very high, despite the preference for DR3 (37)(38)(39)(40). The main associated alleles are DR3 (DRB1*0301) and DR5 (DRB1*1101).…”
Section: Discussionmentioning
confidence: 98%
“…The genetic susceptibility of these diseases is thought to be polygenic. It has been reported that major histocompatibility complex (MHC) gene [4,5], cytotoxic T lymphocyte antigen-4 (CTLA-4) gene [6][7][8], interferong (IFN-g) gene [9,10] and tumor necrosis factor-a (TNF-a) gene [11] polymorphisms are associated with GD and GO. However, none of these associations have been fully confirmed.…”
mentioning
confidence: 99%